The dreaming : waking hours - Wilson, G. Willow, 1982- (The dreaming, 2021)
"One of Dream's heaviest responsibilities is creating nightmares...and he thinks he may have built his next masterpiece in the form of Ruin. But Ruin will live up to his name, in ways that Dream could never expect and creating a spiral of consequences and messes to be cleaned. When Lindy dreams of Ruin-she somehow delivers him unto the waking world! Has anyone checked on Puck lately? Oh no...it looks like he's found someone to stalk too. Sorceress Heather After will have to find a protector for herself...but is she prepared for the deal she'll have to strike once she finds the champion with the dangerous power she needs? With a trip into the realm of Faerie too, you don't want to miss the collection of your dreams!"--